Bounce : Mozart, Federer, Picasso, Beckham, and the science of success - Syed, Matthew (Harper, 2010)
In this thoughtful, provocative book, a former Olympian persuasively demonstrates how sports offer powerful and often overlooked tools with which to explore fundamental subjects, including biology, morality, globalization, culture, gender, race, and economics.